Robotic process automation for future accountants: a threat or asset / Wan Adibah Wan Ismail - Wan Ismail, Wan Adibah (Faculty of Accountancy, 2021)
Robotic Process Automation (RPA) is the use of software to handle rule-based, repeatable tasks currently performed by humans. RPA technology can copy what human is doing manually and make it automated. RPA is not a physical robot, instead it is just a software that is highly powerful to copy the workflow tasks previously done by humans. RPA is sometimes called as the ‘softbot’. RPA as one of the categories that falls under artificial intelligence (AI), is basically a fundamental step towards the far-reaching but less defined artificial intelligence.